Repesentasi Praktik Jurnalisme Investigasi Dalam Film Scoop - Fellin Anggini; Aliasan .; Jufrizal . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This research discusses the representation of investigative journalism practice in the film Scoop, with a focus on how the journalistic work process is constructed through stages such as forming, initial research and observations, determining angles and hypotheses, planning execution strategies, and preparing post-publication scenarios. This film was chosen because it shows the practice of investigative journalism comprehensively, not only as a process of gathering information, but also as an arena involving ethical considerations, institutional pressures, and power relations between the media and sources. This research uses a qualitative approach with Roland Barthes' semiotic analysis method through the stages of denotation, connotation, and myth to interpret symbols, narratives, dialogue, and visual expressions that represent the practice of investigative journalism. Stuart Hall's representation theory is used as the main framework to understand how the meaning of journalism is formed in films, while the concept of investigative journalism is used to strengthen analysis of the media's work process in revealing facts and building public reality. Interpretative-descriptive methodology is applied through observation of key scenes that reflect the stages of journalistic work, from planning to publication. The research results show that investigative journalism is represented as a systematic, collaborative and strategic practice. At the denotative level, the film shows activities such as editorial meetings, team assignments, in-depth research, negotiations with sources, and an intense interview process. At the connotative level, this practice means that investigative journalism is a profession full of pressure, requiring precision, courage and effective communication skills. Meanwhile, at the mythical level, the film builds the ideology that investigative journalism acts as a watchdog journalism whose aim is to demand accountability and voice the public interest.